1997
DOI: 10.1088/0031-9155/42/7/012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of numerically predicted electric field distributions produced by a radiofrequency coil

Abstract: There are safety issues regarding energy deposition within tissues due to radiofrequency fields used in some magnetic resonance (MR) procedures. Procedures should be compliant with guidelines that specify limits to temperature elevation and specific absorption rate (SAR). In general, direct measurement of these quantities in patients is impractical and an alternative approach is to determine SAR from the electric field (E-field) distributions predicted by numerical models. In this initial study the E-field dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…This makes the task of quantification of RF heating (SARs and temperature rises) and its correlation with the electric field more difficult as precise measurement techniques, and rigorous [16] computational methods are required for their evaluation. As MRI RF induced SARs and power deposition in tissues have been reported by many authors [9,[17][18][19][20] using computational electromagnetics, these calculations/simulations along with electric field [16,21,22] and RF heating measurements [23,24] have confirmed temperature changes in biological samples during MRI scans. In this context, the fluorooptic techniques, for instance, have shown that they are capable of relatively accurate temperature measurements [25].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This makes the task of quantification of RF heating (SARs and temperature rises) and its correlation with the electric field more difficult as precise measurement techniques, and rigorous [16] computational methods are required for their evaluation. As MRI RF induced SARs and power deposition in tissues have been reported by many authors [9,[17][18][19][20] using computational electromagnetics, these calculations/simulations along with electric field [16,21,22] and RF heating measurements [23,24] have confirmed temperature changes in biological samples during MRI scans. In this context, the fluorooptic techniques, for instance, have shown that they are capable of relatively accurate temperature measurements [25].…”
Section: Introductionmentioning
confidence: 62%
“…In this work, a probe developed by Taylor et al [21,22] was built and used to measure the transverse electric field (E 1 field) distributions within an empty 8-T (340 MHz) RF head coil and within a saline water phantom loaded in the same coil. Simulations of the same coil and loadings were also performed using an in-house finite difference time domain (FDTD) method [15,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The coil simulations were performed for both coils tuned at 32.13 MHz, and loaded with a pair of cubic samples (14 9 14 9 23 cm) identical to the ones employed for MR measurements and whose dielectric properties meet the American Society for Testing and Material (ASTM) criteria for MR phantom development (e r = 78, r = 0.39 S/m) [22]. The distance between the surface coil plane and the cubic phantom was 2 cm (Fig.…”
Section: Sample-induced Resistance Calculationmentioning
confidence: 99%
“…Successively, we tuned the coil at 31 MHz to measure the electrical conductivity of a 2.4 g/l NaCl solution described in literature for numerically predicting electric field distributions in the phantom material (35). The measured value resulted in 0.46 S/m while the literature reported 0.3865 S/m at 31 MHz and 0.43 S/m for a 2.34 g/l NaCl solution (36), measured to be constant in the range 1.6 KHz to 300 MHz.…”
Section: Estimation Of Electrical Conductivitysaline Solution Concentmentioning
confidence: 99%